Personality and attention bias in adults with a history of childhood trauma, and attenuating effects of mu-opioid agonist buprenorphine on attention bias - Christ, Bjorn U (Department of Psychology, 2014)
The current study compared personality characteristics and cognitive functioning (specifically, attentional bias) in a sample of adults who had experienced childhood trauma (the Trauma group) and a matched healthy control group. The study also examined the possible effects of the mu-opioid agonist buprenorphine on attentional bias in the Trauma group.